REVIEW: How soldier guitars, culture and faith paved way for Bougainville’s peace - David Robie (Asia Pacific Network, 2019)
Soldiers Without Guns: An untold story of unsung Kiwi heroes, documentary, 92min. Director Will Watson. Narrated by Lucy Lawless.